Triploporella ? edgelli n. sp., a new Dasycladalean alga from the Lower Cretaceous of Lebanon. (May 2017) - Maksoud, Sibelle; Granier, Bruno; Azar, Dany
Abstract: The Dasycladalean assemblage of the Jezzinian strata (uppermost Barremian–lowermost Aptian) of Lebanon consists of two organo‐genera and eight genera with eleven species, including eight Triploporellaceae. Although Triploporella marsicana (Praturlon, 1964) was reported by Saint‐Marc from the same interval, it is not found in our material. However, a lookalike, which is herein described as Triploporella ? edgelli n. sp., is identified. This new species has cyst‐containers within the primary segments of its laterals but, because it lacks calcified secondary segments, it is left in open nomenclature. Abstract : Description of a Triploporellacean alga from the Barremian‐Bedoulian strata of Lebanon. This alga has cyst containers as some Triploporella sp. but it lacks calcified secondary laterals